Pilot Protection Scheme of Submarine Cable in Flexible Low-Frequency Transmission System Based on Cross Entropy Algorithm - Weixuan HE; Zhengzhen FAN; Yaotong HUO; Yingyu LIANG (Zhongguo dianli)
There are power electronic converters on both sides of the AC submarine line of flexible low-frequency transmission system, and the fault current characteristics are determined by the converter control strategy, which is different from the traditional synchronous power supply, which will lead to the risk of incorrect operation of the traditional current differential protection. Based on the fault current characteristics of offshore wind power transmission system cable line, this paper analyzes the operational performance of traditional current differential protection and reveals the reasons for the decline of operational performance. In this paper, a novel pilot protection scheme based on cross entropy algorithm is proposed. In this scheme, virtual negative capacitance compensation and negative number processing are carried out on the sampled current of one side, and then the cross entropy between the sampled current and the current of the other side is calculated. According to the change of cross entropy, external and internal faults are judged. The hardware in-loop test results show that the scheme can operate correctly when various types of faults occur in the submarine cable, and has strong resistance to high transition resistance. It can also operate correctly when there are measurement errors in TA. It can be used as a primary protection for flexible low-frequency transmission submarine.